The Economic Effects of Coronavirus (COVID-19) on Jordan - Saraireh, Dr. Shadi Arshid Muslim (The journal of contemporary issues in business and government, 2021)
COVID-19 is observed as a significant economic threat for the economies across the globe. This research paper specifically focuses on the case of Jordon. It evaluates whether COVID-19 crisis has significantly affected the country's economy. Based on the objective, the study applies a quantitative methodology to assess the problem. It assumes stock market performance as a representation of economic performance and examines the impact of coronavirus (COVID-19) on the Jordon's Amman SE General Index price and returns. Considering the sample periods before and during the COVID-19 outbreak, the study finds that the COVID-19 period exhibit both lower index price and index returns at 0.01 level. Similarly, the impact of COVID-19's new cases is significant and negative on the performance of the stock market. Based on the findings, this research recommends to focus on COVID's negative economic implications.